2010
DOI: 10.1002/cncr.24998
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose proton therapy and carbon‐ion therapy for stage I nonsmall cell lung cancer

Abstract: patients with stage I NSCLC were treated with proton therapy or carbon-ion therapy (57 with proton therapy and 23 with carbon-ion therapy) using 3 treatment protocols. In the first protocol, 80 gray equivalents (GyE) of proton therapy was given in 20 fractions, and the second proton therapy protocol used 60 GyE in 10 fractions. For carbon-ion therapy, 52.8 GyE was given in 4 fractions. After achieving promising preliminary results for the first protocol, the authors started to use the second proton therapy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 36 publications
4
98
4
1
Order By: Relevance
“…Hypofractionation with protons and C-ions is under way for NSCLC in several centres. Published TCP data for CPT in NSCLC [39][40][41][42][43][44][45][46] are plotted in Figure 4, along with the curve derived from X-ray SBRT trials. 33,34 CPT TCP are generally consistent with the X-ray SBRT TCP.…”
Section: Hypofractionationmentioning
confidence: 99%
“…Hypofractionation with protons and C-ions is under way for NSCLC in several centres. Published TCP data for CPT in NSCLC [39][40][41][42][43][44][45][46] are plotted in Figure 4, along with the curve derived from X-ray SBRT trials. 33,34 CPT TCP are generally consistent with the X-ray SBRT TCP.…”
Section: Hypofractionationmentioning
confidence: 99%
“…Considering these advantages, C-ion RT is expected to achieve high local control rates without severe adverse events in several types of tumor. For stage I NSCLC, a number of studies of C-ion RT revealed that its efficacy and safety were comparable to SBRT (8)(9)(10). Despite the high rate of local control in C-ion RT for stage I NSCLC, regional lymph node or distant metastasis are relatively common (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…PBT has also been used for stage IA/IB NSCLC, but the clinical evidence for efficacy is limited [4,[18][19][20][21][22]. Nihei et al reported the results of PBT for 37 patients with stage I NSCLC.…”
Section: Clinical Results Of Pbt For Early Stage Non-small-cell Lung mentioning
confidence: 99%